LAJU PERTUMBUHAN INTRINSIK Helopeltis antonii SIGN. PADA BUAH MENTIMUN SEBAGAI PAKAN ALTERNATIF - DJATNIKA K.; I. WAYAN LABA; W. R. ATMADJA (Pusat Penelitian dan Pengembangan Perkebunan, 1998)
Intrinsic growth rate of Helopeltis antonii Sign. (Hemip- tera; Miridae) on cucumberfruit as an alternativefoodThe study on the intinsic rate of natural increase of Helopeltis antonii Sign. On cucumber ruit as an alternative food was conducted in the pest and disease Laboratory, Research Institute for Spice and Medicinal Crops Bogor rom January o June 1998. Helopeltis antonii is well known as the pest of cashew, cacao and tea The objectives of the experiment wee to study the reproduction rate and fecundity of H antonii. The insects were collected from the field of cashew tees in Bogor. A pair of newly emerged adult was eleased into a plastic jar containing cucumber fruit. The fruit was changed daily until the insects died. A newly emerged nymph was eaed individually in a plastic cup containing a peace of cucumber ruit which was renew every 2 days. Birch exponential equation: N,=No.e